A new approach to the measurement of potential quality in grazing systems - Rubino R.; Claps S.; Sepe L. (Analyse technico-économique des systèmes de production ovine et caprine : méthodologie et valorisation pour le développement et la prospective., 2006)
The authors propose a new approach to the evaluation of the potential quality that production Systems and, in particular, grazing can achieve. As a result, the initial proposal is to produce a system for defining the types of quality that are to be measured in the products and, subsequently, to specify for each single product, the most representative parameters and the factors conditioning their content. Ultimately, indicators will be proposed for the monitoring of each production system.
Séminaire du sous-réseau Systèmes de Production du réseau Interrégional FAO-CIHEAM de recherche et développement sur les ovins et caprins, 2005/06/16-18, Seville (Spain)